A brief history of the Baguio sine - Locsin, Ma. Rina A. (2013)
The establishment, growth and death of the stand-alone movie theaters (sine) in Baguio City is narrated from the 1990s to the beginning of the 2000s, noting the context for their establishment and the reasons for their rise and decline. Using Homi K. Bhabha's concept of hybridity, the Baguio sine is then analyzed : first, as a social space initially reflecting the Baguio locals' resistance and accommodation of American colonizer who developed the city as a resort town ; and second as a site of negotiation where the colonized developed their own hybrid identity and culture. This study on the independent movie theaters in Baguio is circumscribed in a domestic setting, allowing for the inclusion of vernacular memory in the construction of history.
Keywords: Motion picture theaters -- Baguio City; Motion pictures -- Baguio City -- History